A Systematic analysis of teachers' strategies for promoting resilience and mental health among elementary students following bullying - Ningrum Perwitasari; Annisa Adelia; Claresta Cleo Sagita; Shifa Putri Azzahra (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
The phenomenon of bullying or violence often occurs anywhere, whether at home, in the workplace, or even in educational environments. A safe and peaceful life is a desire longed for by everyone; therefore, with a balanced life, harmonious relationships can be built. However, the reality is often different for those who become victims of bullying, resulting in serious negative impacts on quality of life and mental health. The method used in this study is a systematic literature review (SLR). Regarding this study, teachers must have strategies to overcome the impacts of bullying, which can disturb psychological well-being, such as causing trauma or even depression. Bullying, which in English is called 'bullying,' is often considered trivial and treated as a normal matter. Therefore, this study focuses on three essential aspects, namely, 1) various types of bullying, 2) strategies for teachers to prevent bullying and its consequences, and 3) causes of bullying and ways to maintain students' mental health after bullying. The articles in this research can be used systematically as references to enhance the resilience of students who experience negative impacts from bullying.